Results of long-term treatment with thrombopoietin receptor agonists of resistant primary immune thrombocytopenia - O. Yu. Vinogradova; M. M. Pankrashkina; L. A. Mukha; A. L. Neverova; M. V. Chernikov; V. V. Ptushkin (Онкогематология)
Background. Thrombopoietin receptor agonists (TORAs), which can imitate the biological effect of thrombopoietin, have shown high efficacy in a number of clinical studies and real clinical practice in patients with resistant primary immune thrombocytopenia (IT). It seems extremely relevant to evaluate the success of using various TORAs in a longterm nonrandomized study and their comparative effectiveness.Aim. To evaluate the longterm efficacy of TORAs (romiplostim and eltrombopag) in patients with primary IT who are resistant to standard therapy, and to determine the clinical and hematological factors predicting the efficacy of TORAs therapy.Materials and methods. The study included 456 patients with primary IT (127 (28 %) men and 329 (72 %) women) who were resistant to standard therapy. atients received TORAs therapy at the otkin Hospital. The median age at the start of TORAs therapy was 59 (9–91) years. Romiplostim was received by 339 patients (95 (28 %) men and 244 (72 %) women), eltrombopag – 117 (32 (27 %) men and 85 (73 %) women).Results. The median duration of TORAs therapy was 78 (1–583) weeks for romiplostim and 59 (1–572) weeks for eltrombopag. uring the TORAs therapy the platelet response was obtained in 89 % (n = 405) of cases in total group of IT patients, in the romiplostim group – in 90 % (n = 306), in the eltrombopag group – in 85 % (n = 99). y the time of data analysis in the total cohort of IT patients, 55 % (n = 253) of patients maintained a sustained platelet response, with a median duration of 159 (2–655) weeks. Among patients receiving romiplostim, these parameters were 59 % (n = 200) and 149 (2–655) weeks, for eltrombopag – 45 % (n = 53) and 240 (24–565) weeks, respectively. The 10‑year overall survival rate with TORAs therapy, regardless of the drug chosen, was 86 %. Negative predictors of achieving a platelet response to romiplostim therapy were identified: ≥2 lines of previous therapy (p = 0.03), a history of splenectomy (p = 0.02). No negative predictors of platelet response to eltrombopag therapy were identified.Conclusion. The longterm efficacy of 2 drugs of the same therapeutic class (TORAs), romiplostim and eltrombopag, in patients with resistant IT was demonstrated in a direct comparative analysis in a nonrandomized study. Clinical and hematological factors predicting the longterm effectiveness of romiplostim were identified.